Three cheers for Tacky - Lester, Helen; Munsinger, Lynn (New York Scholastic Inc., 1994)
Tacky the penguin adds his own unique touch to his team's routine at the Penguin Cheering Contest, with surprising results.
470
Accelerated Reader AR
Keywords: Penguins -- Fiction; Individuality -- Fiction